A strategic framework for devolving responsibility and functions from government to the private sector - Cohen, Steven (2001)
Whether a function should be performed within or outside government is a very broad issue that relates to personal values and views concerning the relationship between individual and state, as well as a complex set of management issues. Without trying to answer those questions here, this article begins from the premise that a particular function has been judged by the political process to be the responsibility of government. The article seeks to develop an approach for government managers to use when deciding whether to perform the function directly in-house or to perform the function indirectly through the use of a non-governmental organization. The first part of this article begins by delineating distinguishing characteristics of government, nonprofit, and private organizations, and then assesses the degree to which those characteristics impede or facilitate the performance of public functions. The article then develops a framework and a method for making privatization decisions. The decision to privatize requires strategic thinking; this article provides an example of how a strategic framework might be applied by analyzing the issues that would be faced in privatizing a key element of New York City's homeless program. - Reproduced
Keywords: Private sector; Privatization